Antioxidant properties, bioaccessibility and bioavailability of polyphenol from Mangifera indica L. (Water Lily Var.) using in vitro model - Zulkifli, Marina (2018)
The fruit of Mangifera indica L. (Water Lily variety) is a mango variety commonly found in Malaysia and Thailand. Its size is about 14 cm length and 7 mm width and a long kidney-shaped. However, limited study done on Water Lily mango pulp related to its quality, digestion and absorption, in which its fate is not totally understand. For the first time, a study on investigating the nutritional composition and physicochemical properties of Water Lily mango pulp were determined. The antioxidant properties of the pulp, together with its polyphenol profile was also evaluated. The bioaccessibility and bioavailability of polyphenol were investigated using an in vitro simulation gastrointestinal digestion model and in vitro Caco-2 cell model, respectively. The nutritional content of pulp was in the order of moisture > carbohydrate > protein > dietary fibre > ash > fat. For sugar analysis, sucrose found to be the highest sugar followed by fructose and glucose whereas for mineral test, potassium was the greatest amount compared to other elements determined such as calcium, sodium, magnesium and iron. Meanwhile, results on physicochemical characteristics indicated that the pulp had high total soluble solid. The extract of Water Lily mango pulp has demonstrated to possess high amount of antioxidant constituents such as polyphenols. The antioxidant capacity as well as its polyphenols profile was investigated by using high performance liquid chromatography (HPLC) and liquid chromatography-mass spectroscopy (LC-MS). The antioxidant capacity of Water Lily pulp extract (WLPE) exhibited a good potential as electron donors and radical scavenger, as determined by Ferric Reducing Antioxidant Power (FRAP) and 1,1- diphenyl-2-picrylhydrazyl (DPPH) assays, respectively. Ten polyphenols were identified and quantified in WLPE with descending order; gallic acid > catechin hydrate > mangiferin > protocatechuic acid > chlorogenic acid > ellagic acid > rutin > myricetin > daidzein > apigenin. In bioaccessibility study, the in vitro simulated gastrointestinal digestion was applied to determine the bioaccessible fraction recovered in two digestion phases; gastric phase and intestinal phase. Among all identified compounds, apigenin was selected as a target compound to be further studied on the bioaccessibility and bioavailability due to its stability in acidic and alkaline environments during gastrointestinal digestion. Results showed that the amount of apigenin after 1 h subjected to acidic gastric condition was significantly reduced (p<0.05) from 2.48 mg/100 dry weight (DW) to 0.5 mg/100g DW. After 2 h exposed to mild alkaline condition, the bioaccessible apigenin increased significantly (p<0.05) to 1.03 mg/100g DW. The percentage bioaccessibility of apigenin was found to be higher in intestinal digestion than gastric digestion with 41.53% and 20.26%, respectively. Investigation on bioavailability was carried out by determining the absorption and transport of bioaccessible apigenin into Caco-2 human intestinal cell using the reliable and sensitive analytical method of LC-MS/MS. Results revealed that the concentration of glucuronidated apigenin lower than apigenin. The apigenin was metabolised inside the cells through glucuronidation process, and cross the monolayer to reach the basolateral sides or effluxed back to the apical side. The permeability coefficient of apigenin from apical to basolateral sides and basolateral to apical sides showed a medium permeability as the value was less than 20 x10-6 cm.sec-1. Since the value of efflux ratio was 1.5, it suggested that the apigenin has been absorbed and transported through the simple diffusion mechanism. Taken together, the findings of present study highlight the nutritional value of Water Lily mango pulp and its valuable compounds. Although the utilisation of in vitro model is not fully responding the physiological and morphological features of human in vivo conditions, it can be a useful tool for evaluating the mechanistic effects of phenolic compound released from the food matrix.